Phylogenomics of the Major Tropical Plant Family Annonaceae Using Targeted Enrichment of Nuclear Genes - Couvreur, Thomas L. P.; Helmstetter, Andrew J.; Koenen, Erik J. M.; Bethune, Kevin; Brandão, Rita D.; Little, Stefan A.; Sauquet, Hervé; Erkens, Roy H. J. (Frontiers in Plant Science, 2019)
Targeted enrichment and sequencing of hundreds of nuclear loci for phylogenetic reconstruction is becoming an important tool for plant systematics and evolution. Annonaceae is a major pantropical plant family with 109 genera and ca. 2450 species, occurring across all major and minor tropical forests of the world. Baits were designed by sequencing the transcriptomes of five species from two of the largest Annonaceae subfamilies. Orthologous loci were identified. The resulting baiting kit was used to reconstruct phylogenetic relationships at two different levels using concatenated and gene tree approaches: a family wide Annonaceae analysis sampling 65 genera and a species level analysis of tribe Piptostigmateae sampling 29 species with multiple individuals per species. DNA extraction was undertaken mainly on silicagel dried leaves, with two samples from herbarium dried leaves. Our kit targets 469 exons (364,653 bp of sequence data), successfully capturing sequences from across Annonaceae. Silicagel dried and herbarium DNA worked equally well. We present for the first time a nuclear gene-based phylogenetic tree at the generic level based on 317 supercontigs. Results mainly confirm previous chloroplast based studies. However, several new relationships are found and discussed. We show significant differences in branch lengths between the two large subfamilies Annonoideae and Malmeoideae. A new tribe, Annickieae, is erected containing a single African genus Annickia. We also reconstructed a well resolved species-level phylogenetic tree of the Piptostigmteae tribe. Our baiting kit is useful for reconstructing well supported phylogenetic relationships within Annonaceae at different taxonomic levels. The nuclear genome is mainly concordant with plastome information with a few exceptions. Moreover, we find that substitution rate heterogeneity between the two subfamilies is also found within the nuclear compartment, and not just plastomes and ribosomal DNA as previously shown. Our results have implications for understanding the biogeography, molecular dating and evolution of Annonaceae.